FOREIGN SCHOLARS, CANADIAN CONTENT: SYMBOLIC POLITICS AND THE SYMONS REPORT - Silva, Edward; Pupo, Noreen; Green, Barry (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1988)
Little is known about Canadian higher educational commissions. To help fill the gap this paper analyzes the Symons Report of the AUCC Commission on Canadian Studies in terms drawn from material and status politics theory. It inspects the origins, method, and responses to the Symons Report. Overall, it interprets the report as a cultural defense of managerial authority in the face of popular attack. It argues that both the managerial defenders and the popular attackers win and consolidate symbolic victories at somewhat different levels. Some limits of the arguments are noted. RÉSUMÉ On ne connaît que peu de choses des commissions d’enseignement supérieur canadiennes. Afin de combler cette lacune, les auteurs analysent le Rapport Symons de la Commission sur les études canadiennes de l’AUCC en termes de documentation, empruntant une démarche axée sur la théorie politique du standing. On y étudie les origines, la méthode et les réactions au Rapport Symons. Dans l’ensemble, les auteurs voient dans le Rapport une défense culturelle de l’autorité des cadres face à une attaque populaire. A leur avis, défenseurs de cadres et contestataires populaires remportent et consolident des victoires symboliques à des niveaux quelque peu différents. Les limites de certains arguments sont soulignées.